Analyzing Students’ Errors and Epistemological Obstacles in Sequences and Series - Marlina Wati; Tina Yunarti; Sugeng Sutiarso (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study investigates students’ errors in solving sequence and series problems using Newman Error Analysis (NEA) and examines the underlying epistemological obstacles. A descriptive qualitative design was applied to 32 eleventh-grade students, with data collected through problem solving tests and semi-structured interviews. The results show that transformation errors were the most frequent (34.4%), followed by process skill errors (25.0%), comprehension errors (21.9%), reading errors (12.5%), and encoding errors (6.2%). These findings indicate that students face significant challenges in translating contextual problems into mathematical models and executing accurate procedures. Furthermore, three types of epistemological obstacles were identified: generalization, conceptual, and intuitive obstacles. This study contributes by integrating error analysis with epistemological perspectives, providing deeper insights into students’ cognitive processes. The findings offer practical implications for designing instruction that emphasizes conceptual understanding and mathematical modeling